Problems of chronology in Gandhāran art : proceedings of the First International Workshop of the Gandhāra Connections Project, University of Oxford, 23rd-24th March, 2017 - Rienjang, Wannaporn,; Stewart, Peter, 1971- (Archaeopress Publishing Ltd, 2018)
'Problems of Chronology in Gandhāran Art' is the first publication of the Gandhara Connections project at the University of Oxford's Classical Art Research Centre. It presents the proceedings of the first of three international workshops on fundamental questions in the study of Gandharan art, held at Oxford in March 2017.